Recovery of activities of daily living in COVID-19 patients requiring intensive care unit or medical care unit: an observational study on the role of rehabilitation in the subacute phase - Notarstefano, Chiara; Bertolucci, Federica; Miccoli, Mario; Posteraro, Federico (Frontiers in Rehabilitation Sciences, 2023)
Purpose This study aims to describe the functional status of a cohort of subacute COVID-19 patients treated in a dedicated rehabilitation unit and to compare functional outcomes between patients previously hospitalized in the intensive care unit (ICU group) and patients assisted in the medical care unit (MCU group). Materials and methods Clinical and functional evaluations were performed at admission and discharge. The functional status was assessed using Barthel index (BI), functional ambulation categories (FAC), trunk control test (TCT), and dysphagia outcome and severity score (DOSS). All patients received multidisciplinary tailored rehabilitation. Results We evaluated 171 patients (with a mean age of 67.7 ± 11.9 years, 117 were males), 110 coming from the ICU (with a mean age of 63.24 ± 10.9 years), and 61 coming from the MCU (with a mean age of 75.75 ± 9.09 years). The ICU group showed a worse functional status at admission compared with the MCU group [BI 2.5 (0–20) vs. 20 (10–60), FAC 0 (0–0) vs. 0 (0–2), TCT 61 (42–100) vs. 100 (61–100), DOSS 5 (1–7) vs. 7 (7–7)] and had significantly longer hospital stay. At discharge, all functional scales were improved with no statistically significant differences between the two groups. Conclusion Early rehabilitation of COVID-19 survivors improves functional recovery closing the initial gap between the ICU and MCU groups. In addition, it is effective to improve the functional outcome reducing the costs for longer-term assistance of COVID-19 patients.